Indicators for the evaluation of a pluviometric network. A technical note - de Bautista, Susana; Alvarado, Joaquín; Barrera, Guillermo; Ferrer, Ronald (Rev. Téc. Fac. Ing. Univ. Zulia, 2011)
In this paper, three indicators of the quality of the information provided by a pluviometric network are defined. It is based on the variation in the time of the correlation coefficient between two stations, the network density and the amount of missing values.